OS2.2 Highly personalized peptide vaccination for patients with newly diagnosed glioblastoma: the GAPVAC trial. (19th September 2018) - Dietrich, P; Wick, W; Hilf, N; Frenzel, K; Gouttefangeas, C; Platten, M; thor Straten, P; Lassen, U; Rodon, J; Bukur, V; Admon, A; van der Burg, S H; et al.
Abstract: Background: There is a need for treatment personalization as every cancer is molecularly unique. In addition glioblastoma (GB) are immunologically regarded as resistant, "cold" tumor with few targetable antigens available from mutations, thus demanding new personalized immunotherapies. So far outside Neuro-Oncology, T cells orchestrate impressive anti-tumor effects with checkpoint inhibitors, but also vaccines. Material and Methods: The GAPVAC consortium established an immunotherapy, for which personalized selection of 2 peptide-based actively personalized vaccines (APVAC) per patient for treatment of newly diagnosed GB was based not only on whole-exome sequencing but also on human leukocyte antigen (HLA)-ligandome analyses providing insight into the actual presentation of relevant epitopes in the tumor. GAPVAC-101 (NCT02149225) enrolled 16 patients in a European phase I feasibility, safety and immunogenicity trial integrated into standard of care. For APVAC1, up to 7 peptides were selected from a trial specific warehouse based on individual biomarker data. Vaccination (i.d.) with GM-CSF and poly-ICLC in 15 patients started with the 1 st adjuvant cycle of temozolomide (TMZ). For APVAC2, analyses revealed a median of 36 somatic, non-synonymous mutations in the patients' tumors. From the 4 th TMZ cycle, 11 patients received APVAC2 with usually 2 de novo antigens per patient selected according to mutation, actual or putative HLA presentation and immunogenicity. Overall 20 APVAC2 antigens incl. 14 mutated were vaccinated. Results: Adverse events were largely reversible injection site reactions and two anaphylactic reactions and one increase in cerebral edema. Short, non-mutated APVAC1 antigens induced sustained CD8 responses with memory phenotype. Mutated APVAC2 antigens induced predominantly CD4 responses of favorable TH1 type. Median PFS and OS were 14.2 and 29 months from diagnosis, respectively, in patients that received ≥1 APVAC vaccination (N=15). Conclusion: Overall, GAPVAC displayed expected safety profiles and high biological activity indicating further development.